Cybersecurity Horizons: Navigating Challenges in the Space Tourism Industry - Ibrahim, Mohamed; Abbas, Sheer (Journal of Legal Sciences, 2026)
The last decade witnessed a dynamic revival in human space exploration, propelled by burgeoning private sector involvement headed by companies like Virgin Galactic, Blue Origin, and SpaceX, catalyzing a global drive toward interstellar colonization aspirations and fostering collaborative efforts between nations and individuals evident in initiatives such as NASA’s Artemis program, China’s Tiangong program, and Russia and India’s aspirations for independent space stations, which extends humanity’s reach into the vast expanse of space beyond Earth’s immediate celestial neighbors. This paper explores the under-addressed but critical domain of cybersecurity challenges in the rapidly advancing space tourism industry. It explains the potential threats posed by cyber-attacks to human spaceflights, specifically in the private sector, including the human factor, social engineering, and technical vulnerabilities. Furthermore, it draws attention to historical incidents in space exploration alongside its sensitive infrastructure. It emphasizes the pressing need for robust cybersecurity strategies to safeguard space tourism missions' security, safety, and integrity. It underscores the importance of collaborative efforts, including international cooperation, continuous monitoring, and enhanced crew training, and developing a comprehensive legal framework. The paper argues that by addressing these challenges proactively and collaboratively, the space tourism industry can demonstrate resilience against evolving cyber threats and improve passenger safety, trust, and accessibility of this nascent but promising sector.